Statistics for economics - Naghshpour, Shahdad ([New York, N.Y.] (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2012)
Statistics is the branch of mathematics that deals with real-life problems. As such, it is an essential tool for economists. Unfortunately, the way the concept of statistics is introduced to students is not compatible with the way economists think and learn. The problem is worsened by the use of mathematical jargon and complex derivations. However, as this book demonstrates, neither is necessary. This book is written in simple English with minimal use of symbols, mostly for the sake of brevity and to make reading literature more meaningful.
Statistics is the science of finding order in chaos -- Introduction -- 1. Descriptive statistics -- 2. Numerical descriptive statistics for quantitative variables -- 3. Some applications of descriptive statistics -- 4. Distribution functions -- 5. Sampling distribution of sample statistics -- 6. Point and interval estimation -- 7. Statistical inference with test of hypothesis -- 8. An introduction to regression analysis -- 9. Conclusion -- Glossary -- References -- Index.
Part of: 2012 digital library.
Includes bibliographical references (p. 187-188) and index.
Also available in print.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat reader.
Title from PDF t.p. (viewed on November 28, 2012).
Keywords: Economics -- Statistical methods; null and alternative hypotheses; standardization; normal distribution function; statistical inference; test statistics; t distribution function; F distribution function; parameter; mean; standard deviation; interpretation and analysis; coefficient of determination; degrees of freedom; sampling distribution of sample statistics; standard error; unbiased; consistent; efficient; central limit theorem; margin of error; individual error; average error; mean squared error; analysis of variance (ANOVA)